Nutrient intake of European adolescents: results of the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. Issue 3 (8th March 2013) - Diethelm, Katharina; Huybrechts, Inge; Moreno, Luis; De Henauw, Stefaan; Manios, Yannis; Beghin, Laurent; González-Gross, Marcela; Le Donne, Cinzia; Cuenca-García, Magdalena; Castillo, Manuel J; Widhalm, Kurt; Patterson, Emma; et al.
Abstract: Objective: An adequate nutritional intake in childhood and adolescence is crucial for growth and the prevention of youth and adult obesity and nutrition-related morbidities. Improving nutrient intake in children and adolescents is of public health importance. The purpose of the present study was to describe and evaluate the nutrient intake in a European sample using the D-A-CH nutrient intake recommendations and the Nutritional Quality Index (NQI). Design: The HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study is a cross-sectional study, the main objective of which is to obtain comparable data on a variety of nutritional and health-related parameters in adolescents aged 12·5–17·5 years. Setting: Eight cities in Europe. Subjects: The initial sample consisted of 3528 European adolescents. Among these, 1590 adolescents (54 % female) had sufficient and plausible dietary data on energy and nutrient intakes from two 24 h recalls using the HELENA-DIAT software. Results: The intakes of most macronutrients, vitamins and minerals were in line with the D-A-CH recommendations. While the intakes of SFA and salt were too high, the intake of PUFA was too low. Furthermore, the intakes of vitamin D, folate, iodine and F were less than about 55 % of the recommendations. The median NQI was about 71 (of a maximum of 100). Conclusions: The intakes of most nutrients were adequate. However, further studies using suitable criteria to assess nutrient status are needed. Public health initiatives should educate children and adolescents regarding balanced food choices.